ANALISIS BAURAN PEMASARAN BUAH STROBERI DI “LUMBUNG STROBERI” DESA PANDANREJO KECAMATAN BUMIAJI KOTA BATU - Restu Pamuji; Istis Baroh; Fithri Mufriantie (Universitas Galuh, 2023)
Strawberry is one of the subtropical fruit products that has great potential to be developed in Indonesia. The problem in this business is that there is no institution that accommodates and markets strawberries so that the marketing network is still between cities and a small part is sent to the city of Surabaya. The objectives of this study are: to analyze the marketing problems of strawberries and the marketing mix of strawberries in the Strawberry Barn, Pandanrejo Village, Bumiaji District, Batu City, in April-May 2022 with the consideration that the location is a center for strawberry cultivation and the majority of the people are strawberry farmers. Marketing problems and marketing mix were analyzed by qualitative descriptive method. The method of determining respondents in this study used purposive sampling. The data used in this study are primary data and secondary data. The results showed that the problem of marketing strawberries is that there is no institution that accommodates and markets strawberries so that the marketing network in the granary is still between cities and a small portion is sent to the city of Surabaya. The weakness of strawberry fruit products is also not durable, spoils quickly, the fruit is soft so special handling is needed by speeding up the shipping process. Lumbung Strawberry has implemented a marketing mix strategy that uses 7P variables, namely product, price, place, promotion, people, packaging and process